High-Altitude Drives the Convergent Evolution of Alpha Diversity and Indicator Microbiota in the Gut Microbiomes of Ungulates - Wang, Xibao; Wu, Xiaoyang; Shang, Yongquan; Gao, Ying; Li, Ying; Wei, Qinguo; Dong, Yuehuan; Mei, Xuesong; Zhou, Shengyang; Sun, Guolei; Liu, Lixian; Lige, Bi; et al. (Frontiers in Microbiology, 2022)
Abstract Convergent evolution is an important sector of evolutionary biology. High-altitude environments are one of the extreme environments for animals, especially in the Qinghai Tibet Plateau, driving the inquiry of whether, under broader phylogeny, high-altitude factors drive the convergent evolution of Artiodactyla and Perissodactyla gut microbiomes. Therefore, we profiled the gut microbiome of Artiodactyla and Perissodactyla at high and low altitudes using 16S rRNA gene sequencing. According to cluster analyses, the gut microbiome compositions of high-altitude Artiodactyla and Perissodactyla were not grouped together and were far from those of low-altitude Artiodactyla and Perissodactyla. The Wilcoxon’s test in high-altitude ungulates showed significantly higher Sobs and Shannon indices than in low-altitude ungulates. At the phylum level, Firmicutes and Patescibacteria were significantly enriched in the gut microbiomes of high-altitude ungulates, which also displayed a higher Firmicutes/Bacteroidetes value than low-altitude ungulates. At the family level, Ruminococcaceae, Christensenellaceae, and Saccharimonadaceae were significantly enriched in the gut microbiomes of high-altitude ungulates. Our results also indicated that the OH and FH groups shared two significantly enriched genera, Christensenellaceae_R_7_group and Candidatus_Saccharimonas. These findings indicated that a high altitude cannot surpass the order level to drive the convergent evolution of ungulate gut microbiome composition, but can drive the convergent evolution of alpha diversity and indicator microbiota in the gut microbiome of ungulates. Overall, this study provides a novel perspective for understanding the adaptation of ungulates to high-altitude environments.